To differentiate y= 2/x
Firstly you get rid of the fraction by taking X to the top(this will make its power negative) giving:
y=2x^-1
From here its just a simple case of carrying out the differentiation:
dy/dx = -2X^-2 or dy/dx = -2/X^2
2006-11-01 04:44:59
·
answer #1
·
answered by Stevie B 2
·
0⤊
0⤋
Think of it as 2x^-1
The differential is -2X^-2
2006-11-01 11:37:26
·
answer #2
·
answered by econdrone 2
·
1⤊
0⤋
First step, put the expression in index form.
2/x = 2x^-1
Then differentiate as usual
dy/dx = -1 *2 x ^-1 -1
dy/dx = -2x^-2
It is usual to express the answer in the form of the question
dy/dx = -2/x^2
2006-11-01 11:39:11
·
answer #3
·
answered by RATTY 7
·
1⤊
0⤋
In my head. I'd get -2/x^2.
2006-11-01 11:49:51
·
answer #4
·
answered by mathematician 7
·
0⤊
0⤋
2/x = 2*x^-1
the derivative would then be:
(-1)*2x^(-1 - 1) = -2/(x^2) or -2x^(-2)
2006-11-01 11:36:47
·
answer #5
·
answered by disposable_hero_too 6
·
2⤊
0⤋
y=2/x
y'=2(-1)/x^2=-2/x^2
2006-11-01 13:37:00
·
answer #6
·
answered by yupchagee 7
·
0⤊
0⤋
y=2/x=2*x^(-1)
y'=nx^(n-1)
therefore, y'=2*(-1)*x^(-2) = -2/x^2
i hope that this helps
2006-11-01 12:15:13
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
3 sq + 6.2x xy
2006-11-01 11:35:50
·
answer #8
·
answered by mannit m 4
·
0⤊
2⤋